La «Scienza della logica» di Hegel: autonomia come emancipazione del pensiero (Lebenswelt. Aesthetics and philosophy of experience., 2019)
With the Science of Logic, Hegel poses a radical challenge to philosophy: a self-presentation of thought that, by not assuming anything outside itself, achieves its self-knowledge. From the possibility of such a project depends that of the autonomy of thought, that is, of a thought that gives itself its own law.Some classical readings consider this enterprise to be unsuccesful or not to be fully accomplished in the Logic. According to Dieter Henrich, Hegel's Logic would fall into a circle, because (although without external assumption) would be burdened by the presupposition of the structure of thought itself, which should rather result from the logical process. For Robert B. Pippin or Terry Pinkard, instead, the instance of autonomy of thought would be realized not in the logic, but only at the level of the spirit.In contrast to such interpretations, we will try to show that precisely in the Logic the thought determines itself as autonomous. In its self-presentation thought, that has itself as its object, produces its own structures, which are not prior to the movement (it produces its own form or law). And once it has come to know itself as such a process, thought ceases to presuppose itself as an object (it emancipates itself) and poses its own form for itself (it gives itself the law).